The Influence of Competence, Conflict Management and Work Stress on the Performance of Employees at the Office of the Revenue Agency South Konawe Regency Area - Baso Silond ae, Andi; Abbas, Bakhtiar; Yuana, Indira; Nur, Muh. (Publikasiku, 2025)
This study aims to determine and analyze the Influence of Competence, Conflict Management and Work Stress on Employee Performance at the Office of the Regional Revenue Agency of South Konawe Regency. The Influence of Competence on Employee Performance at the Office of the Regional Revenue Agency of South Konawe Regency. The Influence of Work Stress on Employee Performance of the South Konawe Regency Regional Revenue Agency Office. This study used quantitative research with the object of the Office of the Regional Revenue Agency of South Konawe Regency. The population and sample in this study used a saturated sample of 35 employees at the South Konawe Regency Regional Revenue Agency Office. The results of this study show that Competence, Conflict Management, and Work Stress have a positive and significant influence on Employee Performance at the South Konawe Regency Regional Revenue Agency Office. Competence has a positive and significant influence on Employee Performance at the Office of the Regional Revenue Agency of South Konawe Regency. Conflict Management has a positive and significant influence on Employee Performance at the Regional Revenue Agency Office of Konawe Regency Selatan. Work Stress has a negative and significant influence on Employee Performance at the Office of the Regional Revenue Agency of South Konawe Regency.